A Determination of fracture toughness in plain concrete specimens by R curve - Hamza Chbani; Bouchra Saadouki; Mostapha Boudlal; Mohamed Barakat (Fracture and Structural Integrity)
Since the last two centuries, concrete has become the number one building material in the world. Therefore, we are interested in studying the mechanical behavior at failure of this material and calculate its toughness.